Convertibility Risk : The Precautionary Demand for Foreign Currency in a Crisis - Mourmouras, Alex (IMF Working Papers; Working Paper ;, 2001)
This paper presents theoretical work linking money demand to the perceptions of households about the risk that domestic currency may become inconvertible or that it may be devalued. An empirical investigation of the size of this effect is carried out using both cross section data and then monthly data for Korea to estimate an augmented demand for money equation. It is found that the fear of inconvertibility arising from the 1997 Korean currency crisis may have caused broad money demand to fall by 4-5 percentage points, equivalent to the loss of reserves of USD 6-72 billion (or about 30 percent of reserves as measured at end-November 1997).